Options for active case detection of visceral leishmaniasis in endemic districts of India, Nepal and Bangladesh, comparing yield, feasibility and costs. - Shri Prakash Singh; Siddhivinayak Hirve; M Mamun Huda; Megha Raj Banjara; Narendra Kumar; Dinesh Mondal; Shyam Sundar; Pradeep Das; Chitra Kumar Gurung; Suman Rijal; C P Thakur; Beena Varghese; et al. (Public Library of Science (PLoS), 2011)
Background The VL elimination strategy requires cost-effective tools for case detection and management. This intervention study tests the yield, feasibility and cost of 4 different active case detection (ACD) strategies (camp, index case, incentive and blanket approach) in VL endemic districts of India, Nepal and Bangladesh. Methodology/principal findings First, VL screening (fever more than 14 days, splenomegaly, rK39 test) was performed in camps. This was followed by house to house screening (blanket approach). An analysis of secondary VL cases in the neighborhood of index cases was simulated (index case approach). A second screening round was repeated 4-6 months later. In another sub-district in India and Nepal, health workers received incentives for detecting new VL cases over a 4 month period (incentive approach). This was followed by house screening for undetected cases. A total of 28 new VL cases were identified by blanket approach in the 1(st) screening round, and used as ACD gold standard. Of these, the camp approach identified 22 (sensitivity 78.6%), index case approach identified 12 (sensitivity--42.9%), and incentive approach identified 23 new VL cases out of 29 cases detected by the house screening (sensitivity--79.3%). The effort required to detect a new VL case varied (blanket approach--1092 households, incentive approach--978 households; index case approach--788 households had to be screened). The cost per new case detected varied (camp approach $21 - $661; index case approach $149 - $200; incentive based approach $50 - $543; blanket screening $112 - $629). The 2(nd) screening round yielded 20 new VL cases. Sixty and nine new PKDL cases were detected in the first and second round respectively. Conclusions/significance ACD in the VL elimination campaign has a high yield of new cases at programme costs which vary according to the screening method chosen. Countries need the right mix of approaches according to the epidemiological profile, affordability and organizational feasibility.